Azeb Amha - Maarten Mous - Graziano Savà (eds.): Omotic and Cushitic Language Studies: Papers from the Fourth Cushitic Omotic Conference, Leiden 10-12 April 2003 - Voigt, Rainer (Aethiopica, 2009)
Review